“ANALISIS PERHITUNGAN RASIO DARI RPM TURBIN KE PUTARAN ROLL GILINGAN PT PG RAJAWALI II UNIT JATITUJUH MAJALENGKA” - Khafid , Ahmad khaerul; Samantha , Yudi (Universitas Majalengka, 2025)
(RPM) from the turbine to the mill roll. An accurate rotational speed ratio is crucialfor improving the efficiency and performance of the milling system. In this study,the rotational speed ratio was calculated based on the turbine RPM and the gearratio between the turbine and the mill roll. The results show that accurate rotationalspeed ratio calculations can help improve milling system performance and reducethe risk of equipment damage. This research can serve as a reference for industriesusing milling systems to improve efficiency and production performance.